Current methodologies available to evaluate the virulence potential among Listeria monocytogenes clonal complexes - Sousa, Mariana; Magalhães, Rui; Ferreira, Vânia; Teixeira, Paula (Frontiers in Microbiology, 2024)
Listeria monocytogenes is a foodborne pathogen that causes listeriosis in humans, the severity of which depends on multiple factors, including intrinsic characteristics of the affected individuals and the pathogen itself. Additionally, emerging evidence suggests that epigenetic modifications may also modulate host susceptibility to infection. Therefore, different clinical outcomes can be expected, ranging from self-limiting gastroenteritis to severe central nervous system and maternal-neonatal infections, and bacteremia . Furthermore, L. monocytogenes is a genetically and phenotypically diverse species, resulting in a large variation in virulence potential between strains. Multilocus sequence typing (MLST) has been widely used to categorize the clonal structure of bacterial species and to define clonal complexes (CCs) of genetically related isolates. The combination of MLST and epidemiological data allows to distinguish hypervirulent CCs, which are notably more prevalent in clinical cases and typically associated with severe forms of the disease. Conversely, other CCs, termed hypovirulent are predominantly isolated from food and food processing environments and are associated with the occurrence of listeriosis in immunosuppressed individuals. Reports of genetic traits associated with this diversity have been described. The Food and Agriculture Organization (FAO) is encouraging the search for virulence biomarkers to rapidly identify the main strains of concern to reduce food waste and economical losses. The aim of this review is to comprehensively collect, describe and discuss the methodologies used to discriminate the virulence potential of L. monocytogenes CCs. From the exploration of in vitro and in vivo models to the study of expression of virulence genes, each approach is critically explored to better understand its applicability and efficiency in distinguishing the virulence potential of the pathogen.